<h2>Answer:</h2>
![10.\text{ Option B is correct}](https://tex.z-dn.net/?f=10.%5Ctext%7B%20Option%20B%20is%20correct%7D)
<h2>Explanation:</h2>
Given the equation expressed as:
![2x+5=8x](https://tex.z-dn.net/?f=2x%2B5%3D8x)
First, we need to calculate the value of "x" from the given expression.
Step 1: Given the equation 2x + 5 = 8x
Step 2: Subtract 5 from both sides:
![\begin{gathered} 2x+5-5=8x-5 \\ 2x+\cancel{5}-\cancel{5}=8x-5 \\ 2x=8x-5 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%202x%2B5-5%3D8x-5%20%5C%5C%202x%2B%5Ccancel%7B5%7D-%5Ccancel%7B5%7D%3D8x-5%20%5C%5C%202x%3D8x-5%20%5Cend%7Bgathered%7D)
Step 3: Subtract 8x from both sides
![\begin{gathered} 2x-8x=8x-8x-5 \\ -6x=\cancel{8x}-\cancel{8x}-5 \\ -6x=-5 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%202x-8x%3D8x-8x-5%20%5C%5C%20-6x%3D%5Ccancel%7B8x%7D-%5Ccancel%7B8x%7D-5%20%5C%5C%20-6x%3D-5%20%5Cend%7Bgathered%7D)
Step 4: Divide both sides by -6
![\begin{gathered} \frac{-6x}{-6}=\frac{-5}{-6} \\ x=\frac{5}{6} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7B-6x%7D%7B-6%7D%3D%5Cfrac%7B-5%7D%7B-6%7D%20%5C%5C%20x%3D%5Cfrac%7B5%7D%7B6%7D%20%5Cend%7Bgathered%7D)
Step 5: Get the value of 12x. Substitute x = 5/6 into the expression to have:
![\begin{gathered} 12x=12(\frac{5}{6}) \\ 12x=\cancel{12}^2(\frac{5}{\cancel{6}^1}) \\ 12x=2\times5 \\ 12x=10 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%2012x%3D12%28%5Cfrac%7B5%7D%7B6%7D%29%20%5C%5C%2012x%3D%5Ccancel%7B12%7D%5E2%28%5Cfrac%7B5%7D%7B%5Ccancel%7B6%7D%5E1%7D%29%20%5C%5C%2012x%3D2%5Ctimes5%20%5C%5C%2012x%3D10%20%5Cend%7Bgathered%7D)
Therefore the value of 12x is 10
Step-by-step explanation:
202·87–100·87–2·87
=99.13
Answer:
![5y^{6}\sqrt{2}](https://tex.z-dn.net/?f=5y%5E%7B6%7D%5Csqrt%7B2%7D)
Step-by-step explanation:
We want to simplify:
![\sqrt{50y^{12}}](https://tex.z-dn.net/?f=%5Csqrt%7B50y%5E%7B12%7D%7D)
We rewrite as:
![\sqrt{2\times25 \times (y^{6})^2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%5Ctimes25%20%5Ctimes%20%28y%5E%7B6%7D%29%5E2%7D)
We split the radical sign to obtain:
![\sqrt{25} \times \sqrt{(y^{6})^2} \times \sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B25%7D%20%5Ctimes%20%5Csqrt%7B%28y%5E%7B6%7D%29%5E2%7D%20%5Ctimes%20%5Csqrt%7B2%7D)
Simplify the square root for the perfect squares to get:
![5y^{6}\sqrt{2}](https://tex.z-dn.net/?f=5y%5E%7B6%7D%5Csqrt%7B2%7D)
Therefore the simplified form is: ![5y^{6}\sqrt{2}](https://tex.z-dn.net/?f=5y%5E%7B6%7D%5Csqrt%7B2%7D)
To find the x-intercept, put in 0 for the y.
0=1/4x-2
2=1/4x
8=x
The x-intercept is 8. The point is (8, 0).
To find the y-intercept, put in 0 for the x.
y=1/4(0)-2
y=0-2
y=-2
The y-intercept is -2. The point is (0, -2).
To graph, find the points on a coordinate plane and draw a straight line through them.
Hope this helps!